A new approach for acoustic visualization using directional impulse response in room acoustics. (March 2016) - Lim, Hansol; Imran, Muhammad; Jeon, Jin Yong
Abstract: A new approach is proposed for investigating the temporal and spatial structures of room impulse responses (IRs) using sound field decomposition. A spherical microphone array was used to analyze the directional characteristics of sound fields through reconstructing the sound fields in an actual chamber hall. To perform directional and spatial characterization of recorded sounds, a plane wave decomposition with an adaptive beamforming technique, such as minimum variance distortionless response (MVDR) spatial spectrum estimation, was employed. Based on the proposed method, a directional impulse response (DIR) was generated in the hall, and the sound level was visualized in a video, which was combined with the viewpoint of each receiver. In addition, the DIR was used to calculate the early energy distribution in three-dimensional directions and the results were represented in the hall plan. This method of acoustic visualization can be used to estimate the effects of architectural design components on the directionality of sounds in rooms. Highlights: A new approach for spatiotemporal analysis is proposed using plane wave decomposition and adaptive beamforming. Directional impulse responses (DIR) were generated for all directions with 1° interval. Acoustic visualization is proposed using DIR combined with the panoramic view of hall in a video form. Early energy distribution (C80 ) was represented using DIR with 15° interval.